Snow algae drive productivity and weathering at volcanic rock-hosted glaciers. (15th February 2019) - Havig, Jeff R.; Hamilton, Trinity L.
Abstract: Earth has experienced periodic local to global glaciation for nearly 3 billion years, providing supra- and subglacial environments for colonization by microbial communities. A number of studies have reported on the role of microbial communities in glacial ecosystems including their influence on element cycling and weathering, but there is a paucity data on volcanic rock-hosted glacial ecosystems. Glaciers on stratovolcanoes in the Pacific Northwest override silica-rich rocks which represent analogues to an early Martian cryosphere. On these glaciers, blooms of photosynthetic snow algae support supraglacial microbial communities as has been observed on snowfields, glaciers, and ice sheets. In subglacial environments of volcanic rock-hosted glacial systems, weathering is driven, at least in part, by carbonic acid, suggesting a link between supraglacial carbon sources and subglacial heterotrophic microbial communities. Here, we report inorganic carbon assimilation and microbial community composition on glaciers across three stratovolcanoes ranging in composition from dacitic to mafic in the Pacific Northwest of the United States to begin to constrain the role of supraglacial primary productivity in subglacial weather processes. These data, coupled to contextual carbon and nitrogen isotope analyses of biomass and aqueous geochemistry, indicate snow algae drive light dependent carbon uptake across supraglacial and periglacial environments. Furthermore, snow algae microbial communities are supported by fixed nitrogen predominantly from deposition via precipitation. Our data highlight intense cycling of carbon and nitrogen driven by supraglacial microbial communities that feeds subglacial microbial communities which in turn may drive weathering processes. These results further underscore the role of glacial ecosystems in global biogeochemical cycling, especially during past global glaciations. Finally, these results lend support for glaciers as refugia for biodiversity on Earth and potentially on other bodies such as Mars where evidence exists for widespread and long-lived cryosphere including glaciers and ice sheets.